How do tax technology and controversy expertise affect tax disputes? - Daniel Dyck; Johannes Lorenz; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2022)
Given the rising number, magnitude, and harshness of tax disputes between firms and tax authorities, firms increasingly call on tax technology and controversy expertise to try to resolve these disputes. This study investigates how tax technology embedded in the firm's Tax Risk Management System (TRMS) and the expertise of tax controversy managers affect dispute outcomes and compliance incentives. Using a game-theoretic model, we derive equilibrium strategies for a tax manager's compliance effort, a controversy manager's dispute resolution effort, and a tax authority's litigation decision. Absent a controversy manager, we find that improving a firm's TRMS quality unambiguously decreases the litigation probability. However, in the presence of a controversy manager, we surprisingly find that improving TRMS quality crowds out compliance efforts and can increase litigation probability. Overall we find that a high-quality TRMS is essential to take advantage of the dispute resolution function of a controversy manager.
Keywords: H25; H26; C72; K34; 330; tax dispute resolution; tax risk management; tax technology; controversy expertise; litigation